ANALYSIS OF THE ONLINE LOGISTIC AND DISTRIBUTIONIN ONLINE SHOP (CASE STUDY: LAZADA AND SHOPEE) - I.G.N.A.A. Bhakta Narayana; Jurisa Jonathan; Liem Gai Sin (AIBPM Publisher, 2018)
Lots of online shops appeared these day, and they all have different methods and promotion in order to satisfy their customer. In Indonesia, there are some online shops that becomes Indonesian people’s favorite, two of them are Lazada and Shopee. These online shop uses online logistic in order to distribute products from manufacturer, which is the one who produce the product, to the end user, which is the customer. We conduct the analysis and comparing of the two online shops’ online logistic. The purpose of this paper is to understand the concept of online logistic and also to compare how Lazada and Shopee apply the theory of online logistic in their distribution. From the purpose, Lazada and Shopee’s information and up-to-date data are needed, and from there, comparing each other’s data in order to know which shop more consumers and good review has can be executed. After that, the authors will analyze the factors in both online shops that related to its logistics and distribution, then the conclusion and feedback that can be used by the online shops. To get the information about Lazada and Shoppee, there are two ways, search by the internet and interview with the customer of both shops. This way, the valid and concrete data can be achieved. Keywords: Analysis, Comparation, Distribution, Lazada, Online logistic, Shopee